Medication adherence in obsessive-compulsive disorders and evaluation of effective adherence support strategies - Pöppel, Sophia; Ziegler, Sina; Bednasch, Klara; Kohls, Elisabeth; Rummel-Kluge, Christine (Frontiers in Psychiatry, 2025)
IntroductionMedication adherence is a critical component in the treatment of psychiatric conditions such as obsessive-compulsive disorder (OCD). Poor adherence is associated with an increased risk of relapse, subsequent (re)hospitalization, and prolonged remission, which ultimately leads to a worse prognosis. This study aimed to assess medication adherence over time in individuals with OCD, identify predictors, and gather patient-reported strategies to maintain adherence.MethodsThis study surveyed N = 100 patients recruited in the outpatient department of a university medical center in Leipzig, Germany, between January 2019 and January 2020 (Ethics Committee approval number: 332/18-ek; date of approval: 25 September 2018). Medication adherence was assessed using indirect (i.e., Drug Attitude Inventory, Medication Adherence Rating Scale) and direct methods (i.e., therapeutic drug monitoring via serum drug concentration). Additionally, the participants reported strategies they found helpful for maintaining adherence.ResultsThe participants exhibited mild impairments in various aspects of functioning despite relatively functional daily lives. Most were prescribed selective serotonin reuptake inhibitors (SSRIs), with a subset receiving combination therapy for treatment-resistant cases. Medication adherence was classified into three categories: 24.4% of the participants were good adherers, 62.2% were partially adherent, and 13.4% were non-adherent. Therapeutic drug monitoring (TDM) indicated that 84.6% of the participants had drug levels within the therapeutic range. Concerns about side effects and doubts regarding the efficacy of the medication were commonly reported, which might contribute to suboptimal adherence. However, no significant associations were found between adherence and sociodemographic or clinical variables, which suggested the need for a more comprehensive approach considering psychosocial factors. Behavioral strategies for maintaining adherence (e.g., incorporating medication into daily routines) were preferred and rated as helpful, while invasive monitoring methods were largely rejected.DiscussionThis study highlights the importance of a multifaceted approach to improving medication adherence in individuals with OCD. While SSRIs remain the primary pharmacological treatment, a significant portion of patients still struggle with adherence. Although TDM provides valuable insights into drug levels, it may not fully capture adherence behavior due to metabolic and behavioral variability. Addressing patient concerns about side effects and medication efficacy, alongside implementing behavioral strategies that integrate medication into daily routines, may improve adherence and enhance treatment outcomes.